2014
DOI: 10.14257/ijca.2014.7.11.37
|View full text |Cite
|
Sign up to set email alerts
|

Management Strategy Based on Genetic Algorithm Optimization for PHEV

Abstract: Aiming at the refitted HAFEI hybrid electric vehicle (HEV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Compared with the unoptimized FLRCS, the braking energy recovery rate was improved, and the fuel consumption and emissions were reduced. In [52], an FLRCS was constructed based on GA optimization. The simulation experiments showed that every kind of gas emission was obviously reduced by 12-47% in an FLRCS based on GA optimization compared to strategy based on the RCS.…”
Section: Fuzzy Logic Rule-based Control Strategymentioning
confidence: 99%
“…Compared with the unoptimized FLRCS, the braking energy recovery rate was improved, and the fuel consumption and emissions were reduced. In [52], an FLRCS was constructed based on GA optimization. The simulation experiments showed that every kind of gas emission was obviously reduced by 12-47% in an FLRCS based on GA optimization compared to strategy based on the RCS.…”
Section: Fuzzy Logic Rule-based Control Strategymentioning
confidence: 99%
“…First, to achieve the real-time speed trajectory on-line, a speed prediction model is built using a recurrent neural network (RNN) [36][37][38]. Specifically, the hybrid optimization method of the genetic algorithm (GA) [39,40] and particle swarm optimization algorithm (PSOA) [41] are utilized to optimize the initial parameters of the prediction model to enhance the speed prediction precision of the model. Then, an ECMS-MPC is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…This method has slower convergence speed, lower the probability of the global value. Non-gradient based algorithm could calculate the global optimal solution without the gradient information of the objective function [7][8][9]. GA has the stronger ability of global searching quickly and parallel computing, so genetic algorithm is suitable for solving the optimization problem of HEV [10][11].…”
Section: Introductionmentioning
confidence: 99%